Simulation of the effects of cryogenic liquid nitrogen jets in Ti6Al4V milling. (6th January 2023) - Albertelli, P.; Strano, M.; Monno, M.
Abstract: In this research, a 3D Finite Element simulation model of Ti6Al4V milling with internal delivery of liquid nitrogen LN2 was developed to understand the effects of the cryogenic jets on the cutting mechanics. The numerical model was thoroughly validated comparing the simulated forces and chip morphologies with the corresponding experimental findings, obtained in different cutting conditions. In both cryogenic and dry conditions, the numerical results were in strong agreement with the experiments. Maximum errors in the average main force estimation and in the distance between chip serrations resulted to be respectively 13 % and 17.6 %. The developed model predicted the forces along other directions within an average error of 13.8 % on their maximum values and 27.7 % on their mean values. Experimental findings showed that the main cutting forces were reduced (on average by 22 %) due to cryogenic cooling, that also produced more damaged and fragmented chips. Moreover, cryogenic cooling averagely reduced (−22 %) the distance between chip serrations. The analysis of the simulation results revealed that cryogenic cooling reduced the tool-chip interface temperature of 150–200 °C due to the simultaneous cryogenic cooling action and to lower (about −35 %) tool-chip friction that limited the associated produced heat that represents at least one-tenth of the overall cutting power. Highlights: A 3D Finite Element model of cryogenic milling of titanium alloy was developed. Cryogenic (with inner LN2 delivery) and dry cutting tests on Ti6Al4V were executed. Experimental forces and chip morphology were used to validate the model. Cryogenic cooling produces lower friction and more fragmented chips. Simulations shows that LN2 allows reducing the cutting temperature of −150 °C.